Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$\sqrt{x} +y = 4$, $\sqrt{y} +x= 6$, find the solution (x,y). $NOTE$ : $\sqrt{4}+1= 4-1$, $\sqrt{1} +4 =1+4$

share|cite|improve this question
$(\sqrt{2}+1) \lt (2+\sqrt{1})$, $(\sqrt{4}+1) \lt (4+\sqrt{1})$ – Rajesh K Singh Aug 9 '12 at 5:09
$\sqrt x=4-y$, $x=y^2-8y+16=6-\sqrt y$, $y=(y^2-8y+10)^2$ gives you an equation of degree 4 in $y$. If you can solve it, you win. – Gerry Myerson Aug 9 '12 at 6:00
Another approach is $y=4-\sqrt x$, $\sqrt y = 6-x$ implies $y=(6-x)^2$. Since $y=y$, we can set the right side of both equations equal to each other. Then we get an 4th degree equation in $\sqrt x$. – Matt Groff Aug 9 '12 at 6:07
let $u=\sqrt{x}, v=\sqrt{y}$. Then $u^2+v=4, u+v^2=6$ Hence $v=4-u^2$. Hence $u+16-8u^2+u^4=6 \iff u^4-8u^2+u+10=0$. Wolframalpha gives some disgusting solutions to this quartic equation: – progressiveforest Aug 9 '12 at 6:07
Beautiful question with ugly answer... – ᴊ ᴀ s ᴏ ɴ Aug 9 '12 at 6:13

This is basically the method which was suggested in the comments above - turning this into a quartic equation. We will see whether someone suggest a substantially more elegant solution.

$$\sqrt{x}+y=4\\ x+\sqrt{y}=6$$

Using the substitution $\sqrt{x}=s$ and $\sqrt{y}=t$ we get: $$s+t^2=4\\ t+s^2=6$$

Which gives $$s=4-t^2=4-(6-s^2)^2\\ (s^2-6)^2+s-4=0\\ s^4-12s^2+s+32=0$$

It should be possible to solve this as a quartic equation, although it would be quite laborious. You can check what WolframAlpha is able to find out here and here

share|cite|improve this answer
great attempt indeed – Rajesh K Singh Aug 9 '12 at 6:20

Let, $\sqrt{x}=s$, $\sqrt{y}=t$

we have, $s^4 -12s^2+s+32=0$, which is a 'biquadratic' equation of the form,


i.e. $$s^4 -12s^2+s+32=(s^2+ks+l)(s^2-ks+m)$$

now by equating coefficients, we have

$$l+m-k^2 = -12, k(m-l) = 1, lm = 32$$

from the first two of these equations, we obtain

$$2m=k^2-12+(1/k), 2l=k^2-12-(1/k)$$

hence substituting in the third equation, the values of l,m,





this is a cubic in $k^2$ which always has one real positive solution and we can find $k^{2}$,$l$,$m$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.